Nanopartículas De Fe3o4@Sio2-Nh2 Funcionalizadas Con Un Péptido Biomarcador De Neuroinflamación Como Potencial Agente De Contraste En Resonancia Magnética (2023)
Mild traumatic brain injuries (mTBI´s) are caused by falls, blows or traffic accidents. These are capable of generating microinflammations on the endothelial cells of the blood-brain barrier, affecting their proper functioning and consequently the correct cerebral homeostasis of the individual.